Tingkat Kepuasan Pasien Pada Pelayanan Balai Pengobatan Gigi di Puskesmas Petanahan Kebumen - Wiworo Haryani; Aulia Nur Atikah; Aryani Widayati (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2017)
Satisfaction is a feeling or perception of patients arising from the health performance that occurs after the patient compared towhat to expect. The number of patients visited Dental Service Center at Petanahan Community Health Center Kebumen inOctober-November 2016 went up and down. This reaserch is aimed to know patients' satisfaction level at the Dental ServiceCenter at Petanahan Community Health Center, Kebumen. The type of research was descriptive research. The researchwas conducted at Petanahan Community Health Center, Kebumen. The number of samples was 40 respondents withdetermination of the sample by purposive sampling. Criteria of respondent were 20-45 years old, graduated from junior highschool (minimum), and willing to be the research respondent. The patients' satisfaction level research was conducted afterthe patient received dental and oral health care and completed a questionnaire containing 20 statements. The resultsshowed the satisfaction level of patients in the category of very satisfied as much as 26 respondents (65%). Patientsatisfaction level seen from the comfort dimension showed 60% of respondents are very satisfied, seen from the dimensionsof reliability and professionalism officials 70% of respondents feel very satisfied and seen from the dimensions ofresponsiveness and empathy 67.5% of respondents feel very satisfied. It can be concluded that the level of patientsatisfaction on Dental Service Center Puskesmas Petanahan Kebumen entered in the category very satisfied as much as 26respondents (65%).